(untitled) (Jurnal Manajemen dan Organisasi, 2019)
The halal cosmetics industry has a very potential trend both globally and nationally. In Indonesia, the halal cosmetics industry is one of the industries that contribute to the improvement of the Islamic economy. Along with the development of public knowledge about organic products that are environmentally friendly and do not contain animal ingredients, the demand of halal cosmetics products are increase.Unfortunately, the great potential of the halal industry cannot be used properly by local brand. This study aims to analyze some factors that related in halal purchasing decisions. The primary data collection in this study was carried out by purposive sampling method which is women workers. Data processing methods include descriptive analysis and Structural Equation Modeling (SEM) analysis with Partial Least Squares (PLS) approach. The results of SEM analysis shown that the Psychological latent variable has a direct positive effect to Purchasing, with a path coefficient of 0.603. Psychological aspects are a relevant factor in the halal cosmetic purchasing as halal using motifs could be reflect fulfillment an attractive confession as female workers.